The Sex-cited Body in Margaret Atwood - Boynton, Victoria (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2002)
In her fiction generally, and particularly in the novel Lady Oracle and the story "The Man From Mars," Margaret Atwood explores the gendered body as surface, in the process exploring the implications in capitalist culture of women either having or not having the "right" surface. By building conflict around the conventions that polarize the "right" surfaces against abject surfaces, Atwood recognizes the trap of "sex-citation" and the possibilities of bodies beyond such a binary. Her reading of "attraction" is just that — a reading — variable and unstable, the body as a "sex-citing" text.